Evaluation of realized investments in Belgrade's and Danube region - Jonel Subić; Lana Nastić; Marijana Jovanović (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
Investments in the economy are the basic driver of economic development of the country, or areas where the investment is made. To accomplish the economic development requires constant investment in development activities carried out in that area, but the limiting factor is shortage of own funds to commercial entities invested in the expansion and modernization of its products. Among the most important problems that arise in the Republic of Serbia are the problem of obtaining funds from favourable financing conditions and unstable market system, especially for agricultural products, which in addition to other macroeconomic indicators show a high risk of investing in the entire economy, as well as in agriculture, as one of the most important sectors of the Serbian economy. Given the importance of this investment research has focused on the area of Belgrade and the Danube area, which has a very favourable geographical position and as such it is a favourable area for investment.
Keywords: 330; investments; economy; agriculture